Structure and optical properties of CdS polycrystalline layers for solar cells based on CdS/CdTe - Khrypunov, G.S.; Kopach, G.I.; Dobrozhan, A.I.; Mygushchenko, R.P.; Kropachek, O.V.; Lyubov, V.M. (Functional Materials, 2019)
Thin CdS films about 200-500 nm thick with stable hexagonal modification with 85-80 % transparency value respectively in the visible and infrared spectrum regions were investigated. The use of the FTO sublayer to obtain heterosystem glass/FTO/CdS by magnetron sputtering does not affect the phase composition of the cadmium sulfide layer and the width of the band gap (Eg = 2.42-2.44 eV). Cadmium sulfide thin films, obtained by direct current magnetron sputtering, can be used as a layer of a wide window layer in thin-film solar cells based on the CdS/CdTe heterosystem.